Central banking for emerging market economies - Vasudevan, A. (New Delhi : Academic Foundation, 2003)
The book discusses Central Banking in emerging economies and focus on the challenges and uncertaintites faced by central bankers in trying to maintain price stability and economic growth in their countries. Topics covered include,Currency and payment system, banker to the banks, banker to the governments, monetary policy in open and closed economies, financial stability, autonomy and organisational issues.
Include bibliographical references and index
lje 16/07/13
Loan
Keywords: Banks and Banking, Central; Emerging markets economies